Response of garlic (Allium sativum) to potassium application in loamy sand alluvial soil - GARG, NAVEEN (The Indian Journal of Agricultural Sciences, 2021)
A 2-year experiment was conducted during rabi 2015-17 at Bathinda to study the response of garlic (Allium sativum L.) to basal application of potassium chloride and foliar application of KNO3 (potassium nitrate) in a loamy sand alluvial soil. The basal application of K2O (50 kg/ha) caused non-significant increase in number of leaves/ plant, bulb weight, number of cloves/bulb, 50-clove weight and bulb yield, and significant but marginal increase in plant height (3.2%), bulb equatorial diameter (2.9%), benefit: cost ratio (12.0%) and A-grade bulb yield (13.7%) over control. The foliar application of KNO3 gave better results in improving growth, bulb and yield parameters by low (4-5%), moderate (8-24%) and high magnitude (43-52%), respectively. The quantum of increase was higher at 3% concentration of KNO3 than at 2% with equal number of sprays at same crop stage. The increase in cured bulb yield exhibited an upward trend with increasing number of sprays from two to five at both concentrations. Although, the highest increase over control in cured bulb yield (42.8%) and bulb weight (24.2%) was recorded by five sprays of KNO3 @ 3% which was at par with four sprays at same concentration, the former gave higher benefit: cost ratio as it produced significantly higher grade-A bulb yield than the latter. Therefore, five sprays of KNO3 @ 3% at 30, 45, 60, 75 and 90 days after sowing may be done to improve yield potential of garlic in loamy sand alluvial soil of South-Western Punjab.